Study the Effect of Dielectric Barrier Discharge (DBD) Plasma on the Decomposition of Volatile Organic Compounds - Qassim Farag, Hiba; Saba J. Kadhem (Iraqi Journal of Physics, 2022)
Recently, research has focused on non-thermal plasma (NTP) technologies as a way to remove volatile organic compounds from the air stream, due to its distinctive qualities, which include a quick reaction at room temperature. In this work, the properties of the plasma generated by the dielectric barrier discharge (DBD) system and by a glass insulator were studied. Plasma was generated at different voltages (3, 4, 6, 7, 8 kV ) with a fixed distance between the electrodes of 5 mm, and a constant argon gas flow rate of (2.5) I/min. DBD plasma emission spectra were recorded for each voltage. The Boltzmann plot method was used to calculate the electron temperature in the plasma ( ), and the Stark expansion method was used to calculate the electron density ( ). The decomposition of organic compounds (cyclohexane) was also studied using DBD plasma. The results showed that the potential difference between the two electrodes has a clear effect on the plasma parameters, as the temperature of the electrons  and the density of electrons  increase with the increase in the potential difference between the two electrodes. The DBD plasma system proved to be a good way to decompose volatile organic compounds, as the results proved the emission of hydrogen gas as one of the dissociation products of cyclohexane.